PROPAGATING CRITICAL READING AND CREATIVE WRITING LITERACY USING READER’S DIGEST MAGAZINES - Wan Zumusni Wan Mustapha; Sheela Paramasivam (Universitas Islam Sumatera Utara (UISU), 2018)
Reading and writing have been seen as solitary, boring and individualized among ESL learners. Hence, teaching and learning critical reading and creative writing, can pose even a challenge to educators and learners of a second language, at all levels. The challenge is even greater in the digital era where students would rather spend time online on gadgets than flipping pages of magazines. As a receptive skill, reading a textbook outside the classroom would be next to impossible. This paper shares how second language educators can use an authentic material like Reader’s Digest magazines to propagate fun, engaging and outdoor critical reading and creative writing activities. It incorporates various elements such as team building, collaborative learning and problem-based learning while engaging students to learn vocabulary, sentence construction and paragraph writing in an outdoor setting.